Efektivitas edukasi dash berbasis audiovisual terhadap sikap dan pengetahuan pada lansia dalam mengontrol hipertensi - Permatasari, Cindi; Inayati, Aini; Sriyati, Sriyati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Hypertension, or high blood pressure, is often referred to as "the silent killer" because it often occurs without symptoms. The non-pharmacological therapy approach, the Dietary Approach to Stop Hypertension (DASH), is highly effective in reducing hypertension. Purpose: To determine the effectiveness of audiovisual-based DASH education on knowledge and attitudes about blood pressure control in elderly hypertensive patients. Method: This study used a quasi-experimental design with a pretest-posttest nonequivalent control group design. The subjects were hypertensive patients at the Baciro Village Elderly Health Post (Posyandu Lansia) and the Ngudi Waluyo Elderly Health Post (Posyandu Lansia) in the intervention group, with a total of 47 elderly hypertensive patients. Data were analyzed using independent sample t-tests and Wilcoxon tests. Results: The DASH diet education for hypertension patients achieved a p-value of 0.001 in the intervention group. A one-week follow-up showed an increase in knowledge scores of 43 participants (91.5%) and attitudes toward the DASH diet in 43 participants (89.4%) with a p-value <0.05. Conclusion: DASH diet education using audiovisual media is effective in changing the knowledge and attitudes of people with hypertension.   Keywords: Knowledge; Attitude; Audiovisual Video; Blood Pressure.   Pendahuluan: Hipertensi atau tekanan darah tinggi, sering disebut sebagai “the silent killer” karena sering terjadi tanpa keluhan. Pendekatan Terapi non farmakologis yaitu Diet Dietary Approach to Stop Hypertension (DASH) sangat efektif dalam menurunkan hipertensi Tujuan: Untuk mengetahui efektivitas edukasi DASH berbasis audiovisual terhadap pengetahuan dan sikap dalam mengontrol tekanan darah pada lansia hipertensi Metode: Penelitian ini menggunakan desain quasi experimental design dengan rancangan pretest-posttest nonequivalent control group design. Subjek penelitian adalah penderita hipertensi di Posyandu Lansia Kelurahan Baciro dan Posyandu Lansia Ngudi Waluyo terdiri atas kelompok intervensi dengan total 47 lansia hipertensi. Analisis data menggunakan uji independent sample t-test dan wilcoxon test. Hasil: Edukasi diet DASH pada penderita hipertensi memperoleh p-value = 0.001di kelompok intervensi. Kemudian follow-up setelah 1 minggu pasca intervensi, terdapat pula peningkatan skor pengetahuan 43 partisipan (91.5%) dan sikap 43 partisipan (89.4%) terhadap diet DASH dengan p-value<0.05. Simpulan: Edukasi diet DASH menggunakan media audiovisual efektif terhadap perubahan pengetahuan dan sikap penderita hipertensi.   Kata Kunci: Pengetahuan. Sikap. Video Audiovisual; Tekanan Darah.